ANALISIS DAN EVALUASI KEPUASAN PENGGUNA SISTEM INFORMASI PERPUSTAKAAN DENGAN MENGGUNAKAN PIECES FRAMEWORK - Supriyatna, Adi (Jurnal Pilar Nusa Mandiri, 2015)
The use of information systems requires setting up and management of a specific nature, so that the system is commonly referred to as management information systems. In which there are a variety of activities ranging from system planning, maintenance, until measurements of performance. In carrying out the necessary information system software and hardware as well as the human operator. Above components should be interconnected so that library activities can run smoothly. To determine whether the components of the information system running properly, should require the evaluation process. The purpose of this study was to evaluate whether the system during run and analyze the strengths and weaknesses of the library information system that has been used for in using the PIECES Framework, as well as to determine whether there is any effect on the level of profitability for the use of the system so that the company can do a follow-up to business prospects to face the global challenges. The method used is the method of analysis PIECES Framework, which consists of point analysis: Performance, Informations and Data, Economics, Control and Security, Efficiency, and Service where the point - the point is a reference evaluation and analysis of an information system. The results of this study indicate that the library information system that is being used already has some advantages and strengths that can support the operations of the library, but there are also some disadvantages and shortcomings so that the library information system still needs to be improved.